Description of Knowledge of Parenting Processes and Quality of Mother-Child Interaction in Yogyakarta, Indonesia - Musyafa, Faiz Indra; Akhmadi, Akhmadi; Haryanti, Fitri (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: The COVID-19 pandemic has caused changes in aspects of knowledge and the quality of mother-child interaction. These changes are a result of the suboptimal and unsustainable implementation of a program. Mothers have faced difficulties in implementing parenting patterns during this pandemic. The objective of this study was to provide an overview of the level of knowledge and quality of mother-child interaction in the parenting process during the COVID-19 pandemic in Kulon Progo, Yogyakarta, Indonesia. Methods: The study employed a quantitative descriptive design in March and April 2023. The participants were mothers with toddlers who had received cadre mentoring in child development in 2018, totalling 57 respondents from the entire village in Kulon Progo, Yogyakarta, Indonesia. Questionnaires on maternal knowledge and the quality of interaction for carers were utilised in this study. The data was described using frequency, percentage, and mean. Results: The mother's level of knowledge was 51.98 (21.43), with a distribution of 45.61% indicating less knowledge and 54.38% indicating good knowledge. The mother’s interaction quality was 51.06 (20.11), with 63.15% indicating good interaction quality and 36.85% indicating less intractable quality. Conclusion: The findings of the study indicated a decrease in the knowledge aspect of mothers during the COVID-19 pandemic, while the quality of mother-child interaction has shown an increase.